iPSC-Derived Microglia as a Model to Study Inflammation in Idiopathic Parkinson’s Disease - Badanjak, Katja; Mulica, Patrycja; Smajic, Semra; Delcambre, Sylvie; Tranchevent, Leon-Charles; Diederich, Nico; Rauen, Thomas; Schwamborn, Jens C.; Glaab, Enrico; Cowley, Sally A.; Antony, Paul M. A.; Pereira, Sandro L.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s disease (PD) is a neurodegenerative disease with unknown cause in the majority of patients, who are therefore considered “idiopathic” (IPD). PD predominantly affects dopaminergic neurons in the substantia nigra pars compacta, yet the pathology is not limited to this cell type. Advancing age is considered the main risk factor for the development of IPD and greatly influences the function of microglia, the immune cells of the brain. With increasing age, microglia become dysfunctional and release pro-inflammatory factors into the extracellular space, which promote neuronal cell death. Accordingly, neuroinflammation has also been described as a feature of PD. So far, studies exploring inflammatory pathways in IPD patient samples have primarily focused on blood-derived immune cells or brain sections, but rarely investigated patient microglia in vitro. Accordingly, we decided to explore the contribution of microglia to IPD in a comparative manner using, both, iPSC-derived cultures and postmortem tissue. Our meta-analysis of published RNAseq datasets indicated an upregulation of IL10 and IL1B in nigral tissue from IPD patients. We observed increased expression levels of these cytokines in microglia compared to neurons using our single-cell midbrain atlas. Moreover, IL10 and IL1B were upregulated in IPD compared to control microglia. Next, to validate these findings in vitro, we generated IPD patient microglia from iPSCs using an established differentiation protocol. IPD microglia were more readily primed as indicated by elevated IL1B and IL10 gene expression and higher mRNA and protein levels of NLRP3 after LPS treatment. In addition, IPD microglia had higher phagocytic capacity under basal conditions - a phenotype that was further exacerbated upon stimulation with LPS, suggesting an aberrant microglial function. Our results demonstrate the significance of microglia as the key player in the neuroinflammation process in IPD. While our study highlights the importance of microglia-mediated inflammatory signaling in IPD, further investigations will be needed to explore particular disease mechanisms in these cells.